Early Warning System on Motorcycle Rider Helmets Using Gyrescope Sensors - Khusnul Azima; Arifah Adani; Herry Setiawan (Brilliance: Research of Artificial Intelligence, 2023)
At this time transportation is one of the important things in human life activities. One of the most widely used transportation is two-wheeled vehicles, especially motorcycles. According to the Ministry of Transportation (Kemenhub) reports that in 2021 the number of accidents caused by drivers who are drowsy is 2,140 incidents. This condition encouraged the author to design an anti-drowsiness helmet to reduce the number of accidents and avoid the possibility of accidents due to drowsy driving. The result of this study was that this tool can provide notification in the form of an early warning to motorbike drivers who are indicated to be drowsy by using a vibrating motor. If the head moves on the front, which is the Y axis 300°-360° and on the X axis the right side 20°-60° and on the left side 300°-335°, then the helmet will vibrate. If the Y and X axes of the helmet are in the normal position, the vibration will automatically turn off, and the helmet will return to normal.